Avaliação do potencial pozolânico da cinza de lodo de águas residuárias por meio de técnicas instrumentais - Rosa, Cristiane Maria da Silveira Thiago [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Currently, there is a great concern for waste originating from sewage treatment plants. The system of wastewater treatment technique based on the activated sludge is widely used throughout the world, and basically consists in the separation of the solid part of the sewage through a dehydration process by centrifugation. The sewage, in a second phase of this process, it is sent to the reactors called Upflow Anaerobic Sludge Blanket (UASB), and, in that place, it is subjected to an anaerobic digestion, generating methane gas and anaerobic sludge. This sludge is sent to centrifuges and later released in buckets and transported to landfill. The final residue of this process has environmental concern since this material has been introduced directly in a landfill without a study on the possibility of other applications. Some applications of this material have been investigated by several researchers, for example, for producing biogas, fertilizers, and power generation. Nowadays, the civil construction industry is looking for the reuse of various types of residues in order to apply in the production of mortar and concrete. Some of them may have a pozzolanic property while others can be used as an addition (filler effect). The objective of this work is to evaluate the pozzolanic potential effect of the wastewater sludge ash through instrumental techniques, aiming at a future application in the production of mortar and concrete. Ashes were obtained after the realization of procedures of transporting, drying, grinding and calcining the sludge wastewater. After the tests of particle size measurement, of loss of mass in fire, of the content of chlorides and of insoluble residues, of diffraction and fluorescence of X-rays, of thermogravimetry, and of scanning electron microscopy, applied to the ashes and to the pastes that was made with them, it was possible to verify that this material has a pozolanic potential ...

Atualmente, observa-se uma grande preocupação com a produção de resíduos oriundos de estações de tratamento de esgoto. O sistema de tratamento de águas residuárias baseado na técnica de lodo ativado é amplamente usado em todo o mundo, e, basicamente, consiste na separação da parte sólida do esgoto por meio de um processo de desidratação por centrifugação. Neste processo, o esgoto, em uma segunda fase, que é enviado para os reatores de UASB (Upflow Anaerobic Sludge Blanket), onde esta sujeita à digestão anaeróbica, gerando gás metano e lodo anaeróbico. Este lodo é enviado para centrífugas e, mais tarde, lançado em caçambas e enviado para aterros sanitários O resíduo final deste processo tem preocupação ambiental, uma vez que este material tem sido lançado diretamente em aterros, sem um estudo sobre a possibilidade de outras aplicações. Algumas aplicações deste material já foram investigadas por diversos pesquisadores, como, por exemplo, para a produção de biogás e fertilizantes, e para a geração de energia. Hoje em dia, a indústria da construção civil está procurando a reutilização de vários produtos para serem aplicados na fabricação de argamassas e concretos. Alguns destes materiais podem apresentar propriedade pozolânica enquantos outros podem ser utilizados como uma adição com caracteristica de filler.O objetivo deste trabalho é avaliar o potencial pozolânico da cinza de lodo de águas residuárias, por meio de técnicas instrumentais, visando uma futura aplicação na produção de argamassa e concreto. Após a realização de procedimentos de transporte, secagem, moagem e calcinação do lodo de águas residuárias, e de ensaios de granulometria, perda de massa em relação ao fogo, de determinação do teor de cloretos, de determinação do teor de resíduos insolúveis, de difração de raios-X e de fluorescência de Raios-X, de Termogravimetria ...
Keywords: Aguas residuais; Lodos de esgoto; Pozolanas; Argamassa; Sewage